Direct postendodontic restoration of teeth with the use of core resins and fiber posts morphological aspects. (In Vitro study) - B. R. Shumilovich; S. G. Ivanov; D. A. Ermilov; E. A. Akhtanin; S. I. Kozadaev; А. Yu. Yurchenko (LLC "Endo Press", 2022)
Relevance. It is known that endodontically treated teeth have a lower survival rate compared to vital teeth. This is due both to changes in the hard tissues of the tooth, and to the use of inadequate technologies for their restoration. Therefore, the methods of restoration of such teeth are very relevant. But their application should be conditioned by their scientific substantiation using fundamental research methods, which determined the relevance of this study.Material and methods. The study of the structural and functional characteristics of the restoration was carried out by scanning electron microscopy in the area of the restoration border, the border of the material-pin insert, the ledge area and the surface of the restoration material. For this purpose, 60 periodontal removed teeth with an IROPZ index of 0.8 or more were used, of which 120 restoration samples were made from the standard form of the composite and 120 restorations from the core-composite using a fiber-optic pin in both groups.Results and discussion. In the course of the study, it was found that the data obtained in the study of the morphology of the restoration in group No. 1 indicate insufficient adaptive properties of the traditional form of the composite (porosity, cohesive fractures, violation of the marginal fit); The results of SEM testify to the advantages of the core-composite, which has a homogeneous, micro-rough, adhesive surface free from technical impurities, suitable for the use of all currently used methods of fixing an orthopedic structure.